Developing Grade 10 Student Learning Achievement of Relation Using Deductive Learning Management with Online Exercises - Minmanee Reangnok; Apantee Poonputta (Journal of Educational Issues, 2024)
The purposes of the study were 1) to investigate the effectiveness of deductive learning management with online exercises on grade 10 students learning achievement of mathematical relations; and 2) to investigate students’ satisfaction with the learning management. The study was conducted in a one-group pretest-posttest design. The participants were 41 Thai grade 10 students learning mathematics. The cluster random sampling method was employed in the participant selection process. The instruments were a learning management plan designed in a deductive learning management, a learning achievement test, and a satisfaction questionnaire. The effectiveness of the deductive learning management on students’ learning achievement of mathematical relation was assessed by considering the participant’s performance while learning in the class and at the end of the class. The statistics used in the data analysis were percentages, mean scores, standard deviation, a paired t-test, and an effectiveness test (E1/E2) with the determining criteria of 75/75. The results of the study indicate that the deductive learning management plan with online exercises was capable of improving grade 10 students’ learning achievement of mathematical relations. Moreover, it also brought about a satisfying experience learning the concept. The study contributed to the area of mathematics education as it provided an example to support the use of the deductive learning management on learners with limited mathematic skills.